Effects of a Physical Training Program on the physical capabilities of University Youth - Corozo Palma, Baldomero; Hinostroza Carriel, Edgar Roberto (Scientific Journal: Physical Conditioning and Social Health, 2026)
Introduction: Physical training is an important part of university students’ overall growth, especially for those who play sports or do other fun things. Objective: To examine the impact of a physical training regimen on the physical abilities of young university students. Methodology: This descriptive study will examine the impact of physical training on the physical capacities of students from the Faculty of Physical Activity Sciences at the University of Guayaquil, employing non-probabilistic convenience sampling and assessing flexibility, strength, speed, power, and endurance through standardized tests. Results: Some young university students perform adequately on certain physical tests; however, a substantial number necessitate a more targeted training regimen to markedly enhance their physical abilities. Discussion: Training programs that help students become more flexible, stronger, faster, and more durable can not only help them do better in sports, but they can also help them feel better overall.